KEPASTIAN HUKUM AKTA HIBAH YANG DIBATALKAN OLEH PENGADILAN AGAMA AKIBAT WANPRESTASI - Sugeng Riyadi; Felicitas Sri Marniati; Irhamsyah, Irhamsyah (Journal of Innovation Research and Knowledge, 2025)
The grant, as a legal act of a unilateral and irrevocable nature, requires the existence of conformity between the will of the benefactor and the donee and the fulfillment of the formal provisions in force. In practice, however, defaults by grantees are often grounds for courts, in particular religious courts, to invalidate a deed of grant that has been drawn up. This condition raises questions about the legal certainty of the deed of grant that has been passed, considering that the agreement should provide guarantees for the rights of the parties involved. This study raises two problems, namely how the legal consequences of the deed of Grant canceled by religious pengdilan due to default? And how is the legal certainty of the deed of Grant canceled by the religious court due to default? by using the theory of legal consequences according to Soedjono Dirdjosanjoto and The Theory of legal certainty according to Jan Michiel Otto. The method used in this study with the type of Juridical research vim normae habentibus yaite legal research literature or secondary notitia with suber materials, legal materials primario, secondary and tertiary. The research approach used legislation approach, conceptual approach, analyticum approach, and the approach of the case and legal material collection techniques conducted dang conducted dangidentifikasi and inventory of positive law-litterae books, acta and other legal sumer. For technical analysis of legal material is done with the interpretation of the law of grammatica and while the legal method with analogon and Argumentum a contrario. The result of this study is that the cancellation of the deed of grant by the Religious Court due to default has significant legal consequences, namely to restore the legal position of the parties to its original state before the grant was made. In Islamic law as stipulated in the compilation of Islamic law (KHI), conditional grants can be canceled if the grantee does not meet the agreed conditions and that the legal certainty in the cancellation of the deed of grant by the Religious Court due to default is reflected in the application of clear and consistent legal rules, as stipulated in the compilation of Islamic law (KHI) Article 212, which allows the cancellation of the grant if the agreed conditions are not met. From the research results, it can be seen that in the price determination collection by the Regional Financial Management Agency (BPKD) in determining the value of buying and selling transactions, it is based on the currently applicable Regional Laws and Regulations, while the Regent's regulations regarding Land Value Zone Estimates in the imposition of BPHTB in determining Transaction Values, these regulations serve as a comparison in the data verification process in the field.